2005
DOI: 10.1074/jbc.m503313200
|View full text |Cite
|
Sign up to set email alerts
|

Induction of OGG1 Gene Expression by HIV-1 Tat

Abstract: To identify the cellular gene target for Tat, we performed gene expression profile analysis and found that Tat up-regulates the expression of the OGG1 (8-oxoguanine-DNA glycosylase-1) gene, which encodes an enzyme responsible for repairing the oxidatively damaged guanosine, 8-oxo-7,8-dihydro-2-deoxyguanosine (8-oxodG). We observed that Tat induced OGG1 gene expression by enhancing its promoter activity without changing its mRNA stability. We found that the upstream AP-4 site within the OGG1 promoter is respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 56 publications
1
30
0
1
Order By: Relevance
“…Although AP-4 was initially identified as a cellular protein that binds to the simian virus 40 (SV40) enhancer and activates the viral late gene transcription (21), transcriptional repression by AP-4 was reported in a number of other genes including angiotensinogen (21) and E7 oncoprotein of human papillomavirus type 16 (23). In addition, we recently found that AP-4 negatively regulates transcription of 8-oxo guanine DNA glycosylase 1 (OGG1) gene (24). However, because AP-4 sites are not located adjacent to the TATA box in these promoters, the molecular mechanism of its repressive action is yet to be clarified.…”
Section: Human Immunodeficiency Virus Type 1 (Hiv-1)mentioning
confidence: 99%
See 3 more Smart Citations
“…Although AP-4 was initially identified as a cellular protein that binds to the simian virus 40 (SV40) enhancer and activates the viral late gene transcription (21), transcriptional repression by AP-4 was reported in a number of other genes including angiotensinogen (21) and E7 oncoprotein of human papillomavirus type 16 (23). In addition, we recently found that AP-4 negatively regulates transcription of 8-oxo guanine DNA glycosylase 1 (OGG1) gene (24). However, because AP-4 sites are not located adjacent to the TATA box in these promoters, the molecular mechanism of its repressive action is yet to be clarified.…”
Section: Human Immunodeficiency Virus Type 1 (Hiv-1)mentioning
confidence: 99%
“…Immunoprecipitation and Immunoblot Assays-The experimental procedures for immunoprecipitation and immunoblotting were performed as described (24,27). Briefly, cells were harvested with lysis buffer (25 mM HEPES-NaOH, pH 7.9, 150 mM NaCl, 1.5 mM MgCl 2 , 0.2 mM EDTA, 0.3% Nonidet P-40, 1 mM dithiothreitol, 0.5 mM phenylmethylsulfonyl fluoride).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…27 After treatment with HDACi, the cells were incubated with an oxidation-sensitive fluorescent probe 2 0 , 7 0 -dichlorofluorescein diacetate (H 2 -DCFDA) (Molecular Probes Inc., Eugene, OR, USA) at a final concentration of 5 mM for 30 min. The cells were washed and resuspended in PBS, and then ROS amount was measured by flowcytometry.…”
Section: Detection Of Rosmentioning
confidence: 99%